Mean stability and between-session reliability of cycling biomechanics variables in elite pursuit cyclists - Williams, D.; Dunn, M.; Worsfold, P.; Newton, D.; Faulkner, S. H.; d`Andrea, F.; Wheat, J. (Sports Biomechanics, 2025)
The purpose of this study was to determine the number of crank revolutions required to obtain stable mean values of sagittal plane biomechanics variables, and the between-session reliability of these variables, whilst cyclists used an aerodynamic position. Eighteen elite cyclists completed a 3-min maximal bout on a cycling ergometer. Lower-limb kinematic and kinetic data were captured using 2D motion capture and force pedals. Raw data were filtered using a 4th order Butterworth low-pass filter (6 hz) and interpolated to 100 points per revolution. The middle 60 revolutions of each trial were extracted and 37 discrete and 15 time-series variables were calculated. Mean stability was assessed in all participants, and between-session reliability was analysed in a subset of 11 participants. Sequential averaging indicated more revolutions to stability than iterative intra-class correlation coefficients. Crank kinetics were more stable than joint kinematics and kinetics. For stable discrete and time-series variables, 30 and 38 revolutions are recommended, respectively. Between-day reliability for all variables was moderate to excellent, and good to excellent for crank kinetics and joint kinematics variables. Hip flexion-extension and ankle dorsiflexion kinetics were least reliable. Researchers and applied practitioners should consider these findings when planning, and interpreting results from, cycling biomechanics interventions.